Involvement of Welding Technology Students in Entrepreneurship - Mohd Yatim, Luqman; Rozali, Mohd Zulfadli; Mat, Mohd Yatim (Research and Innovation in Technical and Vocational Education and Training, 2022)
Entrepreneurship is one of the important sectors in the development and progress of a country. In Malaysia, economic development is accelerating but entrepreneurial activities have not yet received good response among the community, especially among youths and teenagers. Entrepreneurial activities are also still less attractive among students in Vocational Colleges, especially in the Welding Technology program. In addition, the level of entrepreneurial readiness among graduates from TVET institutions is also at a low level. Thus, a study was conducted to determine the tendency of Welding Technology entrepreneurial involvement among Vocational College students in the state of Terengganu. A total of 67 diploma students in Welding Technology were selected as sample. Questionnaire as research instrument includes 34 items. Statistical Package for Social Science (SPSS) version 26.0 was used to calculate the mean, standard deviation, frequency, percentage and t-test. The results of the descriptive analysis found that student involvement on aspects of interest, motivation and knowledge are at a high level. While for the results of t-test showed that there is significant difference between male and female students on involvement in entrepreneurship.